Faktor-Faktor yang Mempengaruhi Motivasi Petani dalam Mengembangkan Apel di Kecamatan Tutur Kabupaten Pasuruan: Factors Influencing Farmers' Motivation in Developing Apples in Tutur District, Pasuruan Regency - Wardani, Tiara Puspa; Yektiningsih, Endang; Mubarokah, Mubarokah (Jurnal Ilmiah Manajemen Agribisnis, 2024)
Since 2018, apple production in East Java has been threatened with extinction due to the very cheap price of apples at the farmer level. On the other hand, the presence of imported apples has made local apples less competitive, thus affecting farmers' motivation to farm apples. This study aims to obtain a description of apple farmers and analyze the factors that influence farmers' motivation in farming apples. The research location is in Tutur District, Pasuruan Regency, while the analysis method used is descriptive and multiple regression methods. The results of the study concluded that the age of farmers is still classified as productive age, with an average education of high school, 19.3 years of experience, and an average land area of ​​16.9 hectares. Meanwhile, the factors that significantly influence motivation are education level, self-confidence, farming capital, mastery of technology, and the number of extension services that have been attended.